Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to find the derivative of $y= (1-x^{-1})^{-1}$ to make it simple I use the chain rule and

$$u = 1-x^{-1}$$

$$y = u^{-1}$$

$$y' = -1u^{-2}u' = -1(1-x^{-1})^{-2}(x^{-2})$$

The problem is that this is not what my book gets and I am wondering if there is some strange power rule I overlooked or some other way to do this problem that gives me a different answer, or maybe I just need to factor is out somehow.

share|cite|improve this question
I do not see the difference. – user138246 May 5 '12 at 18:01
I'm sorry, I misread the question. – David Mitra May 5 '12 at 18:04
Jordan, when you subsituted 'back' for $u^{-2}$, you forgot the $\;^{-2}$ part. – copper.hat May 5 '12 at 18:10
I have that on my paper, I just typed it up wrong. – user138246 May 5 '12 at 18:10
Most likely, another case where the book gives a simplified answer: $$-1(1+x^{-1})^{-2}x^{-2}= {-1\over (1-{1\over x})^2}\cdot {1\over x^2} = {-1\over x^2\cdot(1-{1\over x})^2} = {-1\over \bigl( x(1-{1\over x})\bigr)^2} = {-1\over (x-1 )^2} .$$ – David Mitra May 5 '12 at 18:17
up vote 3 down vote accepted

$$y = \left( 1 - x^{-1} \right)^{-1} = \frac1{1 - \frac1x} = \frac{x}{x-1} = 1 + \frac1{x-1}$$ Hence, $$y' = - \frac1{(x-1)^2}$$

To proceed through you method of using chain rule, setting $u = (1-x^{-1})$, we have that $y = u^{-1}$. Hence, $$y' = -\frac{u'}{u^2}.$$ Note that $$u' = \frac1{x^2}.$$ Hence, we get that $$y' = - \frac{1/x^2}{(1-x^{-1})^2} = - \frac{1/x^2}{(1-1/x)^2} = - \frac{1/x^2}{(x-1)^2/x^2} = - \frac1{(x-1)^2}$$

The error you made was that you did not write $u^{-2}$ correctly. $\displaystyle u^{-2} = \frac1{(1-x^{-1})^2}$

share|cite|improve this answer
I see how that is correct, but I do not see why my way of doing it is incorrect. It seems to follow all the rules. – user138246 May 5 '12 at 18:05
I do not follow the second to last part where the x^2 dissapears. – user138246 May 5 '12 at 18:12
@Jordan $$(1-x^{-1})^2 = (1-1/x)^2 = (x-1)^2/x^2.$$ Hence, $$\frac{1/x^2}{(x-1)^2/x^2} = \frac1{(x-1)^2}.$$ – user17762 May 5 '12 at 18:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.